Unveiling the role of Programmed Cell Death Ligand-1 (PDL-1) expression in cervical squamous cell carcinoma: Clinical insights and pathological implications - Sulistiawati, Yuniarni; Arifuddin, Sharvianty; Syahrir, Syahruni; Masadah, Rina; Zainuddin, Andi Alfian (Acta Biomedica Atenei Parmensis, 2026)
Background: Squamous Cell Carcinoma Cervix (SCC) is a major contributor to cancer-related mortality, closely linked to chronic HPV infection. Programmed Cell Death Ligand-1 (PD-L1) has surfaced as a prospective biomarker in several cancers, including cervical squamous cell carcinoma (SCC); however, its clinical and pathological relevance in untreated patients has not yet been thoroughly investigated. Methods: This cross-sectional study included 66 untreated patients diagnosed with cervical SCC, with clinicopathological data and formalin-fixed paraffin-embedded tissue samples collected from Universitas Hasanuddin Teaching Hospital. PD-L1 expression was evaluated using the Tumor Proportion Score (TPS) and categorized as negative (<1%), weakly positive (1–9%), and strongly positive (≥10%). Bivariate methods were used to investigate at the associations between PD-L1 expression and tumor characteristics including stage, differentiation, lymphovascular space invasion (LVSI), and tumor size. Results: Strong PD-L1 expression (≥10%) was significantly more frequent in locally advanced and metastatic stages (p = 0.036). The highest level of PD-L1 expression was observed in tumors which were poorly differentiated; Whereby 84.9% of these tumors exhibited strong expression. No significant correlation was found between PD-L1 expression and LVSI or tumor size. Host factors including age, sexual history, parity, and contraceptive use demonstrated no correlation with PD-L1 expression. Conclusion: The study showed that PD-L1 expression is associated with advanced stages and poor differentiation in cervical SCC, pointing to its potential role in guiding future treatment decisions